The prehistoric artefacts of Northern Ireland - Welsh, Henry (Archaeopress Archaeology, 2022)
'The Prehistoric Artefacts of Northern Ireland' is the last in a trilogy of monographs, designed to provide a baseline survey of the prehistoric sites of Northern Ireland. The first monograph investigated prehistoric burial sites and the second explored the sites of prehistoric life. Following the same format as its predecessors, this monograph considers the prehistoric artefacts that have been found in Northern Ireland.